Warfare and Social Change in non-State Societies of the Predynastic Nile Valley - Gayubas, Augusto (2015)
The emergence of leadership and chiefdoms in the Predynastic Nile Valley has been a topic of interest among researchers. Authors who have dealt with the issue tend to focus their research mainly on the economic and administrative aspects, lacking a serious consideration of conflict, and particularly warfare. Nevertheless, archaeological testimonies seem to suggest a close relation between the emergence of socio-political hierarchies and the realm of war in the Predynastic Nile Valley. The aim of this paper is to briefly consider this issue by evaluating the available archaeological evidence.